2007
DOI: 10.5038/2375-0901.10.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality Attributes Affecting Customer Satisfaction for Bus Transit

Abstract: In this article a tool for measuring customer satisfaction in public transport

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
198
1
9

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(229 citation statements)
references
References 16 publications
3
198
1
9
Order By: Relevance
“…That is why recent years have seen the development of derived importance methods based on CSS (Weinstein, 2000;Cavana et al, 2007;Pakdil and Aydin, 2007;Eboli and Mazzulla, 2007;Joewono and Kubota, 2007;Dell'Olio et al, 2010;Nurul--Habib et al, 2011;Jen et al, 2011) and from stated preference surveys (Hensher and Prioni, 2002;Hensher et al, 2003;Eboli and Mazzulla, 2008a;2008b;Dell'Olio et al, 2011;Cirillo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…That is why recent years have seen the development of derived importance methods based on CSS (Weinstein, 2000;Cavana et al, 2007;Pakdil and Aydin, 2007;Eboli and Mazzulla, 2007;Joewono and Kubota, 2007;Dell'Olio et al, 2010;Nurul--Habib et al, 2011;Jen et al, 2011) and from stated preference surveys (Hensher and Prioni, 2002;Hensher et al, 2003;Eboli and Mazzulla, 2008a;2008b;Dell'Olio et al, 2011;Cirillo et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, research on similar issues regarding the quality of transit service perceived by bus users has confirmed this assumption. For example, Eboli and Mazzulla (2007) found that perceived quality attributes of bus service had an impact on customer satisfaction, and Joewono and Kubota (2007) also found a significant relationship between overall satisfaction and loyalty to use the transit service in the future. Jen and Hu (2003) concluded that passengers' repurchase intentions were determined by their perceived value of the bus service.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can be said that structural equation models are a give set of causal relationship which are formed as a combination of theories and statistical dependency patterns. Structural equation system is generally done using maximum likelihood method (Eboli & Mazzulla, 2007). There are common programs for implementing structural equation method that Lisrel software will be used in this study.…”
Section: Methodsmentioning
confidence: 99%